Association of Poor Childhood Fear Conditioning and Adult Crime - Gao, Yu; Raine, Adrian; Venables, Peter H.; Dawson, Michael E.; Mednick, Sarnoff A. (The American journal of psychiatry, 2010)
ObjectiveAmygdala dysfunction is theorized to give rise to poor fear conditioning, which in turn predisposes to crime, but it is not known whether poor conditioning precedes criminal offending. This study prospectively assessed whether poor fear conditioning early in life predisposes to adult crime in a large cohort. MethodElectrodermal fear conditioning was assessed in a cohort of 1,795 children at age 3, and registration for criminal offending was ascertained at age 23. In a case-control design, 137 cohort members with a criminal record were matched on gender, ethnicity, and social adversity with 274 noncriminal comparison members. Statistical analyses compared childhood fear conditioning for the two groups. ResultsCriminal offenders showed significantly reduced electrodermal fear conditioning at age 3 compared to matched comparison subjects. ConclusionsPoor fear conditioning at age 3 predisposes to crime at age 23. Poor fear conditioning early in life implicates amygdala and ventral prefrontal cortex dysfunction and a lack of fear of socializing punishments in children who grow up to become criminals. These findings are consistent with a neurodevelopmental contribution to crime causation.